Media Portrayal of EU Commission and Its Leaders: A Content Analysis of Spanish Press (1976–2024) - Gallardo-Agudo, Ángel; García-Borrego, Manuel; Roses-Campos, Sergio (MDPI, 2024)
The role of the media is key in mediating civil society and its political representatives in EU institutions. In this context, this paper aims to describe the representation of the European Commission, one of the EU’s most important institutions, and its leaders by two leading Spanish newspapers. In order to address this objective, an automated content analysis was carried out on 13,340 news items published between 6 June 1976 and 15 February 2024 in El País (social democratic media) and ABC (conservative, monarchist media). The sample was subjected to a sentiment analysis as well as topic modeling. The latter method made it possible to identify five predominant issues on the agenda: Economy, Foreign Affairs, Internal Politics, Spanish Politics, and the Future of the EU. The average sentiment, which is close to neutral, has tended slightly toward the negative over the years, although the current president, Ursula von der Leyen, has the highest rating of all the leaders studied. Both El País and ABC provide more negative coverage of the EU when leaders of their ideological opposition govern, a phenomenon that can weaken the European model and encourage political drifts with consequences that are difficult to predict in the medium term.
Keywords: Comisión Europea - En los medios de comunicación social; European Commision; European Union; Media coverage; Spain; Press